Multimodal imaging features of high-grade endometrial stromal sarcoma with pulmonary and nodal metastases: a case report and literature review - Tan, Huayun; Zhang, Tingting (Frontiers in Medicine, 2025)
BackgroundHigh-grade endometrial stromal sarcoma (ESS) is an aggressive tumor that poses significant diagnostic challenges, particularly when associated with multifocal metastases. Multimodal imaging, including ultrasound, computed tomography (CT), and magnetic resonance imaging (MRI), plays a critical role in diagnosis.Case presentationA 51-year-old woman presented with abnormal vaginal bleeding and pelvic pain. Ultrasound revealed an 8 × 12 × 17 cm heterogeneous mass located in the uterine body and cervix. CT scans showed metastatic pelvic lymphadenopathy and pulmonary nodules. MRI demonstrated a T2-hyperintense lesion with myometrial and cervical invasion, along with restricted diffusion on diffusion-weighted imaging (DWI) and apparent diffusion coefficient (ADC) mapping. Pathological analysis confirmed high-grade ESS.ResultsMultimodal imaging successfully differentiated high-grade ESS from benign uterine lesions by identifying aggressive features such as ill-defined margins on ultrasound, areas of necrosis on CT, and restricted diffusion on MRI. The patient was diagnosed with stage IVB (T3bN1M1) high-grade ESS, due to pelvic lymph node involvement and multiple pulmonary metastases.ConclusionHigh-grade ESS is prone to distant metastasis. MRI with DWI and ADC mapping is crucial for assessing tumor cellularity and local invasion, while CT is effective for detecting metastases. Future staging protocols should integrate contrast-enhanced MRI and positron emission tomography–computed tomography (PET–CT) for comprehensive assessment.